2020
DOI: 10.1101/2020.02.07.938662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of the motor cortex transcriptome supports microgial-related key events in amyotrophic lateral sclerosis

Abstract: 400w)Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by the degeneration of upper and lower motor neurons. A major neuropathological finding in ALS is the coexistence of glial activation and aggregation of the phosphorylated transactive response DNA-binding protein 43-kDa (pTDP43) in the motor cortex at the earliest stages of the disease. Despite this, the transcriptional alterations associated with these pathological changes in this major vulnerable brain region ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…An extensive body of evidence has suggested that glia contribute to the neurodegeneration observed in ALS and FTD (9,10,(110)(111)(112)(113). Transcriptional assessments and proteomic approaches across the ALS/FTD spectrum have reported robust glia signatures and glia protein modules, respectively, emphasizing a glia involvement in inflammation and contribution to disease (109,(113)(114)(115).…”
Section: Discussionmentioning
confidence: 99%
“…An extensive body of evidence has suggested that glia contribute to the neurodegeneration observed in ALS and FTD (9,10,(110)(111)(112)(113). Transcriptional assessments and proteomic approaches across the ALS/FTD spectrum have reported robust glia signatures and glia protein modules, respectively, emphasizing a glia involvement in inflammation and contribution to disease (109,(113)(114)(115).…”
Section: Discussionmentioning
confidence: 99%
“…Among the non-control patients, 84% were classified as having a moderate or severe condition in the transcriptome experiments and 90% in the proteome experiments. In total, transcriptomic data of 39 studies (Blalock et al, 2004 , 2011 ; Zhang et al, 2005 ; Dunckley et al, 2006 ; Lesnick et al, 2007 ; Liang et al, 2007 ; Scherzer et al, 2007 ; Simunovic et al, 2009 ; Cox et al, 2010 ; Elstner et al, 2011 ; Dumitriu et al, 2012 , 2016 ; Feyeux et al, 2012 ; Berchtold et al, 2013 ; Hokama et al, 2014 ; Riley et al, 2014 ; Calligaris et al, 2015 ; Dijkstra et al, 2015 ; Labadorf et al, 2015 ; Magistri et al, 2015 ; Prudencio et al, 2015 ; Raman et al, 2015 ; Ring et al, 2015 ; Kapeli et al, 2016 ; Lin et al, 2016 ; Scheckel et al, 2016 ; Lim et al, 2017a , b ; Gagliardi et al, 2018 ; Mehta et al, 2018 ; Stopa et al, 2018 ; Mathys et al, 2019 ; Meyer et al, 2019 ; Otake et al, 2019 ; Swindell et al, 2019 ; Switońska et al, 2019 ; Al-Dalahmah et al, 2020 ; Dols-Icardo et al, 2020 ; Higginbotham et al, 2020 ) and proteomic data of 22 studies were acquired (Fang et al, 2009 ; van Dijk et al, 2012 ; Varghese et al, 2013 ; McQuade et al, 2014 ; Riley et al, 2014 ; Collins et al, 2015 ; Dumitriu et al, 2016 ; Hondius et al, 2016 ; Ratovitski et al, 2016 ; Lachén-Montes et al, 2017 , 2019 ; Seyfried et al, 2017 ; Umoh et al, 2018 ; Zhang et al, 2018 …”
Section: Methodsmentioning
confidence: 99%